2019
DOI: 10.1029/2019ja026627
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Neutral Wind Response Times During High Geomagnetic Activity Above Svalbard

Abstract: It has previously been shown that in the high‐latitude thermosphere, sudden changes in plasma velocity (such as those due to changes in interplanetary magnetic field) are not immediately propagated into the neutral gas via the ion‐drag force. This is due to the neutral particles (O, O2, and N2) constituting the bulk mass of the thermospheric altitude range and thus holding on to residual inertia from a previous level of geomagnetic forcing. This means that consistent forcing (or dragging) from the ionospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In fact, recent studies (Conde et al, 2018;Zou et al, 2018) have certainly shown this to be the case, observing a rapid (<20 minutes) neutral wind response during auroral activity. This is much shorter than previous estimations (on the order of a few hours) during periods of little or no precipitation (Kosch et al, 2010;Joshi et al, 2015;Billett et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In fact, recent studies (Conde et al, 2018;Zou et al, 2018) have certainly shown this to be the case, observing a rapid (<20 minutes) neutral wind response during auroral activity. This is much shorter than previous estimations (on the order of a few hours) during periods of little or no precipitation (Kosch et al, 2010;Joshi et al, 2015;Billett et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
“…Thus, there are often large delays (on the order of hours) before velocity changes in the high latitude plasma translate fully into the neutral wind (e.g. Billett et al, 2019). Traditionally, a quantitative time delay is determined by calculating the time for the neutral wind to accelerate to 1/e of the plasma velocity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Billett et al. (2019) estimated the neutral wind response time to a change in plasma convection at high‐latitudes to be roughly 75–90 min, depending on the strength of the event. Consequently, ion heating events may be more common when the IMF is highly variable and the convection pattern is frequently reconfigured.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the response time of thermospheric density to energy injection during geomagnetic storms, which contributes to study for how long Joule heating might be enhanced (Billett et al, 2019), is also an important topic in magnetosphere‐ionosphere/thermosphere coupling studies. To quantify this response time, we take the time lag between the peak of thermospheric density and the peak of Joule heating (“time lag” hereafter) as the probe for each geomagnetic storm case.…”
Section: Introductionmentioning
confidence: 99%